Study of cutting forces on machinability properties of gray cast iron using new ceramics cutting tools - Souza, J. V C; Nono, M. C A; Oliveira, R. M.; Ribeiro, M. V. [UNESP]; Silva, O. M M (Trans Tech Publications, 2008)
During gray cast iron cutting, the great rate of mechanical energy from cutting forces is converted into heat. Considerable heat is generated, principally in three areas: the shear zone, rake face and at the clearance side of the cutting edge. Excessive heat will cause undesirable high temperature in the tool which leads to softening of the tool and its accelerated wear and breakage. Nowadays the advanced ceramics are widely used in cutting tools. In this paper a composition special of Si3N4 was sintering, characterized, cut and ground to make SNGN120408 and applyed in machining gray cast iron with hardness equal 205 HB in dry cutting conditions by using digital controlled computer lathe. The tool performance was analysed in function of cutting forces, flank wear, temperature and roughness. Therefore metal removing process is carried out for three different cutting speeds (300 m/min, 600 m/min, and 800 m/min), while a cutting depth of 1 mm and a feed rate of 0.33 mm/rev are kept constant. As a result of the experiments, the lowest main cutting force, which depends on cutting speed, is obtained as 264 N at 600 m/min while the highest main cutting force is recorded as 294 N at 300 m/min.
Keywords: Ceramics cutting tools; Cutting forces; Flank wear; Roughness; Temperature; Advanced Ceramics; Cutting depths; Cutting edges; Cutting speeds; Dry cuttings; Excessive heats; Gray cast irons; High temperatures; Mechanical energies; Metal removing; Rake faces; Shear zones; Tool performances; Cast iron; Ceramic materials; Computer control systems; Cutting; Machine tools; Machining; Mechanical properties; Metal casting; Metal cutting; Metal working tools; Powder metals; Powders; Sintering; Cutting tools